ANALISIS KADAR KALSIUM DAN BESI PADA DAUN TANAMAN BAYAM MERAH (Alternantheraamoena Voss) DAN DAUN TANAMAN BAYAM KAKAP (Amaranthus hybridus L) SECARA SPEKTROFOTOMETRI SERAPAN ATOM - Ahmad Gazali Sofwan; Siti Nurbaya; Adiansyah Adiansyah; Pontisari Sitanggang (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Spinach (Amaranthus spp) is a leaf vegetable plant that is highly nutritious and favored by all levels of society. According to information, spinach plants can be used as an additional intake in the prevention of osteoporosis (bone loss) and anemia (lack of blood) because of the high calcium and iron content in them. Two types of spinach are known in the community, namely red spinach (Alternanthera amoena Voss) and spinach snapper (Amaranthus hybridus L). The purpose of this study was to determine the levels of calcium and iron in red spinach and snapper spinach leaves. The assay was carried out using an atomic absorption spectrophotometer with an air-acetylene flame. Quantitative analyzes were carried out at wavelengths of 422.7 nm for calcium and 248.3 nm for iron. The results showed that the levels of calcium and iron obtained with the levels of calcium and iron listed in the literature were different. The results also showed that there were differences in calcium and iron levels between red spinach and snapper spinach. Calcium levels in red spinach and snapper spinach leaves were 26.8016 mg/100g and 24.2759 mg/100g, respectively. The levels of iron in red spinach and snapper spinach leaves were 714.2621 mg/100g and 236.5369 mg/100g, respectively.